Utilitasi Buah Maja menjadi Pestisida Nabati dan Pupuk Organik pada Kelompok Pemuda Hipma Desa Maggenrang - Rosdaliani, Andi; Trisnowali, Andi; Muhammad Irfan Taufan Asfar, Andi; Muhammad Iqbal Akbar Asfar, Andi; Nurannisa, Andi; Wahdania; Arya Harahap, Topan (LPPM UNIVERSITAS LANCANG KUNING, 2023)
Scattered maja fruits are the main problem in Pettungnge Hamlet, Maggenrang Village, Kahu Sub-district, Bone Regency, South Sulawesi Province. Maja fruits in Pettungnge Hamlet are usually left lying around and even thrown into the river by partners because they have an unpleasant smell. This will certainly add to the problem of pollution of the river water ecosystem. Therefore, the implementation of community service was carried out to transform maja fruit into natural control materials and organic fertilizers with three main stages, namely tudang seppo (counseling and socialization), training, and mentoring. The results obtained showed an increase in partner knowledge and skills related to partner knowledge in utilizing maja fruit, maja fruit production, and marketing with an increase of 90% each for partner ability to utilize maja fruit, 90% in the ability to make natural control materials and organic fertilizers, and 80% in partner knowledge in marketing. In addition, the improvement of partner skills can also build partner entrepreneurial spirit.